The Influence of Customer Value and Customer Experience and Niche Marketing on Customer Satisfaction at Daydream Studio Illustration Company - Kadek Sitha Ananda Laura Pratiwi; Ni Luh Putu Agustini Karta; Ni Luh Komang Julyanti Paramita Sari (Publikasi Indonesia, 2025)
This study examines the influence of customer value, customer experience, and niche marketing on customer satisfaction at Daydream Studio, an illustration company. The research aims to identify whether customer value, customer experience, and niche marketing significantly affect customer satisfaction, providing insights for service improvement and strategic marketing. Using quantitative methods and hypothesis testing, the study found that all three variables—customer value, customer experience, and niche marketing—have a positive and significant impact on customer satisfaction. The results show that customer value has the strongest influence, as indicated by a t-value of 7.691 and a significance level of 0.000, confirming a robust positive correlation. Customer experience also demonstrates a significant positive effect (t-value 2.531, significance 0.012), as does niche marketing (t-value 4.243, significance 0.000). These findings are consistent with previous research, reinforcing the importance of these factors in enhancing customer satisfaction within creative service industries. The study concludes that improving customer value, delivering memorable experiences, and implementing effective niche marketing strategies are crucial for increasing customer satisfaction at Daydream Studio.